Analisis Dexametason Jamu Pegal Linu di Lubuk Pakam dengan Metode Spektrofotometri - Cucu Arum Dwi Cahya; Sri Rezeki Anggriani (Jurnal Indah Sains dan Klinis, 2023)
Background: Chemical drugs are prohibited from being contained in traditional medicine doses. Based on BPOM findings in 2015-2017, almost 100 traditional herbal medicine products contain medicinal chemicals (BKO), including dexamethasone. Objective: Study to determine dexamethasone levels and the level of control in herbal medicine for rheumatic pain in the Lubuk Pakam area. Method: The UV-Fis spectrophotometric method was used for quantitative analysis. Meanwhile, for qualitative analysis, the reagents used were the addition of anhydrous acetic acid and concentrated sulfuric acid. Results: Analysis with the addition of this reagent showed that 5 samples contained dexamethasone. UV-Fis spectrophotometric analysis showed dexamethasone levels in samples A1 to A5 were 4.069; 4,229; 4,416; 11,788; and 5,270 mg/g. Conclusion: The research results showed that all five samples contained Dexamethasone at certain levels in the Lubuk Pakam area, North Sumatra